The Effect Of Leadership And Satisfaction On Employee Engagement In Catering Asy'uro Mojokerto - Irwanu Firmansyah, Moch.; Dewi Ruspitasari, Widi (Publisher Cv. Inara, 2022)
This study aims to determine the effect of leadership on job involvement and the effect of satisfaction on job involvement and also the influence of leadership on employee satisfaction at Catering Asy'uro Mojokerto. This research is associative and the data collection technique uses primary data in the form of questionnaires distributed to all employees who work in the company with a population of 30 and the sampling technique uses saturated sampling. The results showed that leadership has a positive and significant influence on employee job involvement and employee satisfaction.